Household Inability to Make Ends Meet: What Changed in The First Year of the COVID-19 Pandemic in Poland? - Hanna DUDEK; Agnieszka WOJEWÓDZKA-WIEWIÓRSKA (Communications of International Proceedings, 2023)
In this paper, we explore the issue of the inability to make ends meet among Polish households. We analyze the occurrence of this phenomenon in the year before and the first year of the COVID-19 pandemic's onset. We aim to identify the socioeconomic factors behind the occurrence of this phenomenon. To achieve this purpose, we apply the logistic regression model. We use the 2019-2020 cross-sectional data from the European Union Statistics on Income and Living Conditions (EU-SILC) survey. We found that the inability to make ends meet increased during the analyzed period. In addition, our results revealed that essential factors affecting the examined phenomenon are household type, education, degree of urbanization, and the presence of disabled and unemployed people in the household. We found that single-parent households, whose members were poorly educated, disabled, and unemployed, experienced particular difficulties in making ends meet.
Keywords: poverty; household; logistic regression; the COVID-19 pandemic